An investigation into the potential role of brain angiogenesis inhibitor protein 3 (BAI3) in the tumorigenesis of small-cell carcinoma: a review of the surrounding literature. (4th July 2017) - Thomas, Michael; Snead, David; Mitchell, Daniel
Abstract: Brain angiogenesis inhibitor protein 3 (BAI3) is from the adhesion group of seven-transmembrane spanning G protein-coupled receptors (GPCRs) and has been identified via gene expression profiling as being upregulated in small-cell lung cancer (SCLC) tumors. It has subsequently been validated as a sensitive and specific immunohistochemical marker for SCLC, helping to differentiate these tumors from morphologically similar large-cell neuroendocrine (LCNEC) malignancies. It is, however, still unclear as to the role BAI3 proteins might play in SCLC and indeed how they might contribute to tumorigenesis. Interestingly, the pattern of staining observed on immunohistochemistry was in fact nuclear as opposed to the membranous staining pattern expected of transmembrane-bound molecules. This fact has lead the authors to believe that the protein receptor is structurally altered in SCLC and that this modification may confer different behavioral properties that contribute toward tumorigenesis. Nuclear localization is not unique to BAI3 and has been reported in a number of GPCRs and frequently correlates with survival outcomes. BAI3 has the potential to act as target for pharmaceutical intervention inline with developing trends in molecular pathology aiming to provide personalized, treatment regimes based on tumor-specific mutation profiles. The adhesion group of the GPCR superfamily is still poorly understood. We present a review of the existing literature regarding the role they play in both physiological and disease states and the mechanisms by which they influence a range of cellular processes.